As Unidades FitoecolÃgicas do MunicÃpio de Itapipoca/Ce: Fatores Condicionantes do Estado de ConservaÃÃo - AntÃnio SÃvio MagalhÃes de Sousa (2009)
This research aims to examine the conservation status and level of environmental degradation of Itapipoca. It is located in the geographical middle region north of Ceara, and has an area of 154.416 hectare. The research was divided into three stages: I) acquisition phase was carried out literature review and geo from production techniques and scientific field work and data collection, description of plant communities and analysis; II) phase analysis was characterized components of the landscape historical, geographical, and of the conservation status; III) phase synthesis (aggregation and integration) of data obtained and data extracted from the analysis phase were characterized and defined eight Phyto-ecological Unit in Itapipoca, highlighting the forms of use and occupation. Phyto-ecological Units are: 1. Open rainforest Montana (Humid Forest) 2. Semi-deciduous forest deciduous submontane (Dry Forest), 3 Forest mixed dicot-palmae the river plains (Varzea), 4. Caatinga trees and shrubs dense submontane (Dense Caatinga vegetation), 5. Caatinga open scrub depression sertaneja (Caatinga vegetation Open) 6. Mixed deciduous forest of coastal tableland, and pre-coastal (deciduous Vegetation Sub-Board), 7. Evergreen forest swamp lowland river floodplains (mangrove), and 8. Training shrub-herbaceous rear of dunes, beach strip and post-beach (sandy coastal vegetation pioneer). An important reason for conducting the research is the lack of work on the massive Uruburetama this area is very degraded compared to other regions of Ceara, mainly associated with the use of agricultural activity and use of inappropriate areas such as river banks (flooded vegetation ), in steep slopes of the mountain forest (Wet and Dry Forest) and flat areas (Dense Caatinga vegetation). It can be found remnants of protected areas, eligible for protection, which required the development of conservation practices in all units phyto-ecological. So, it appears at the end of the research need to establish protected areas in order to protect the vegetation and fauna, and even damage to recover degraded areas, seeking alternatives for maintenance and protection of natural heritage for a better performance of environmental services and the functioning of ecological systems. It is proposed subsidies for the creation, management and monitoring of conservation areas, highlighting the importance of scientific knowledge and community participation for identifying these areas, considering the particularities of each region. The basis for protection should be regulated in the Brazilian Forest Code, the National System of Protected Areas, and relevant environmental legislation.